www.phdkozosseg.hu - Presentation of the scientific community portal - Szontágh, Krisztina (The Hungarian Journal of Marketing and Management, 2019)
In this study the functions of the community site are presented. This site have been developed according to the needs of the target audience. The implementation of services provided by the PhD community site took place based on the results of expert interviews, focus group discussions with students, scientific literature researches, statistical and database analysis, website analysis and questionnaires with PhD students. In the study preparatory work was descibed and the importance ofthe optimalization tasks are highlighted. During the presentation of the scientific community site’s structure the focus was on those functions which support the cooperations. After this, the experiences of the operation and planned development for the future are presented.